+0  
 
0
220
1
avatar
12a+3(a-2)-(a-5)
pls kürzen
Guest Apr 24, 2012
 #1
avatar
0
12a+3(a-2)-(a-5)
12a+3(a-2)-(a-5)=12a + 3(1a+(-2)+-1(1a+(-5a)
=12a+3(1a)+3(-2)+-1(1a)+-1(-5a)
=12a+3a+-6+-1a+5a
=(12a+3a+-1a+5a)+-6
=19a+-6

So the final anwser is 19a+(-6)
Guest Apr 25, 2012

14 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.